Yacht Marinas Investment Attractiveness and Ways to Improve it - Nikolay Vasilyevich Kovalev (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article examines the yacht marinas investment attractiveness and its characteristics. It analysis the main factors influencing the attractiveness of this business, and ways to improve it.